Implementation of planning, organizing, actuating, and controlling (POAC) management functions in a community-based karate dojo - Cynthia Nur Cahyani; Eval Edmizal; Yendrizal Yendrizal; Septri Septri (Global Econedu, 2026)
The ability to manage an organization effectively is recognized as an important factor determining results at club-level sports. However, most studies about organization management in sports focus on large urban sports clubs based in Western countries and not many empirical works address the management function of small, local martial arts clubs in developing countries. How the four traditional management functions planning, organizing, actuating and controlling (POAC) are carried out in small community-based martial arts organizations located in developing regions is still unknown. Purpose: By exploring stakeholders views on the use of POAC-based management in a karate training center in West Pasaman Regency of Indonesia, this paper gives a first picture of a local club management situation that has, until now, never had any performances or data on management documented. Methods: A study that describes a specific situation quantitatively without drawing generalizations was done. As the total population of people involved (20) was rather small, all people that participated: athletes, coaches and administrators, were chosen for a survey through Total Sampling (a census of the entire available population, i.e., complete enumeration rather than qualitative data saturation). A questionnaire with the Likert-type format was used asking for opinion on the four domains of the POAC theory. The results were shown as mean figures, percentiles and norm-referenced distribution. Reliability (Cronbach's alpha) and validity evidence for the questionnaire were not formally assessed in this study; this is acknowledged as a limitation and discussed further below. Results: Stakeholders' perceptions on the entire POAC implementation score were between 176 and 188 (mean, 182.3 and standard deviation, 3.71). When using this study's categories of norms, 45% of the responders assessed the implementation as